Updated Efficacy Results from XELOX1/NO16966, a Randomized Phase 3 Trial in First-Line Metastatic Colorectal Cancer - Alexander, Lori (MD Conference Express, 2007)
This article discusses multiple studies using capecitabine plus oxaliplatin (XELOX), 5-fluorouracil (5-FU), leucovorin, and oxaliplatin (FOLFOX-4), and Infusional 5-FU/LV (FOLFOX-6), as well as the the MOSAIC and XELOX-1 Trials for the treatment of metastatic colorectal cancer.